ABC of resuscitation - Nolan, Jerry; Perkins, Gavin D.; Soar, Jasmeet (ABC series, 2013)
"This book is a practical guide to the latest resuscitation advice for the non-specialist, and covers the core knowledge on the management of patients with cardiopulmonary arrest"--Provided by publisher